Chronic Endurance Exercise Impairs Cardiac Structure and Function in Middle-Aged Mice with Impaired Nrf2 Signaling - Shanmugam, Gobinath; Narasimhan, Madhusudhanan; Conley, Robbie L.; Sairam, Thiagarajan; Kumar, Ashutosh; Mason, Ronald P.; Sankaran, Ramalingam; Hoidal, John R.; Rajasekaran, Namakkal S. (Frontiers in Physiology, 2017)
Nuclear factor erythroid 2 related factor 2 (Nrf2) signaling maintains the redox homeostasis and its activation is shown to suppress cardiac maladaptation. Earlier we reported that acute endurance exercise (2 days) evoked antioxidant cytoprotection in young WT animals but not in aged WT animals. However, the effect of repeated endurance exercise during biologic aging (WT) characterized by an inherent deterioration in Nrf2 signaling and pathological aging (pronounced oxidative susceptibility - Nrf2 absence) in the myocardium remains elusive. Thus, the purpose of our study was to determine the effect of chronic endurance exercise-induced cardiac adaptation in aged mice with and without Nrf2. Age-matched WT and Nrf2-null mice (Nrf2–/–) (>22 months) were subjected to 6 weeks chronic endurance exercise (25 meter/min, 12% grade). The myocardial redox status was assessed by expression of antioxidant defense genes and proteins along with immunochemical detection of DMPO-radical adduct, GSH-NEM, and total ubiquitination. Cardiac functions were assessed by echocardiography and electrocardiogram. At sedentary state, loss of Nrf2 resulted in significant downregulation of antioxidant gene expression (Nqo1, Ho1, Gclm, Cat and Gst-α) with decreased GSH-NEM immuno-fluorescence signals. While Nrf2–/– mice subjected to CEE showed an either similar or more pronounced reduction in the transcript levels of Gclc, Nqo1, Gsr, and Gst-α in relation to WT littermates. In addition, the hearts of Nrf2–/– on CEE showed a substantial reduction in specific antioxidant proteins, G6PD and CAT along with decreased GSH, a pronounced increase in DMPO-adduct and the total ubiquitination levels. Further, CEE resulted in a significant upregulation of hypertrophy genes (Anf, Bnf and β-Mhc) (p<0.05) in the Nrf2–/– hearts in relation to WT mice. Moreover, the aged Nrf2–/– mice exhibited a higher degree of cardiac remodeling in association with a significant decrease in fractional shortening, pronounced ST segment and J wave elevation upon CEE compared to age-matched WT littermates. In conclusion, our findings indicate that while the aged WT and Nrf2 knockout animals both exhibit hypertrophy after CEE, the older Nrf2 knockouts showed ventricular remodeling coupled with profound cardiac functional abnormalities and diastolic dysfunction.